Experience and Expression of Social Isolation by Inner-City High Rise Residents. Issue 3 (19th August 2014) - Chile, Love Mngohol; Black, Xavier M; Neill, Carol
Abstract : Purpose: The purpose of this paper is to examine the significance of social isolation and the factors that create social isolation for residents of inner-city high-rise apartment communities. We critically examine how the physical environment and perceptions of safety in apartment buildings and the inner-city implicate the quality of interactions between residents and with their neighbourhood community. Design/methodology/approach: We used mixed-methods consisting of survey questionnaires supplemented by semi-structured interviews and focus group discussions using stratified random sampling to access predetermined key strata of inner-city high-rise resident population. Using coefficient of correlation we examine the significance of the association between social isolation, age and ethnicity amongst Auckland's inner-city high-rise residents. Findings: We found the experience and expression of social isolation consistent across all age groups, with highest correlation between functional social isolation and 'being student', and older adults (60+ years), length of tenure in current apartment and length of time residents have lived in the inner-city. Research limitations/implications: As a case study, we did not seek in this research to compare the experience and expressions of social isolation in different inner-city contexts, nor of inner-city high-rise residents in New Zealand and other countries, although these will be useful areas to explore in future studies. Practical implications: This study is a useful starting point to build evidence base for professionals working in health and social care services to develop interventions that will help reduce functional social isolation amongst young adults and older adults in inner-city high-rise apartments. This is particularly important as the inner-city population of older adults grow due to international migration, and sub-national shifts from suburbs to the inner-cities in response to governmental policies of urban consolidation. Originality/value: By identifying two forms of social isolation, namely functional and structural social isolation, we have extended previous analysis of social isolation and found that 'living alone' or structural social isolation did not necessarily lead to functional social isolation. It also touched on the links between functional social isolation and self-efficacy of older adults, particularly those from immigrant backgrounds.